Escalation in Ukraine: Conflicting interpretations hamper international diplomacy - Sabine Fischer (Stiftung Wissenschaft und Politik (SWP), 2014)
Russia and the West apply diametrically opposed interpretations of the crisis in Ukraine and the role of international actors. This lack of a shared understanding of events hampers international efforts to resolve the crisis through negotiations. The differences are rooted in opposing narratives about the development of regional and international relations during the past two decades. When formulating Western policy it is important to take account of the Russian narrative and the logic it creates. (SWP Comments)
Keywords: 320